Association of a femoral neck T score with knee joint osteophyte formation but not with skeletal muscle mass - Wu, Kuan-Ting; Wang, Yu-Wei; Wu, Re-Wen; Huang, Chung Cheng; Chen, Ying-Chou (Clinical rheumatology, 2023)
Background Osteophyte formation is an important radiographic sign of osteoarthritis (OA) and limited joint motion in knee osteoarthritis patients. Some studies revealed relationships of osteophyte formation with a high bone mineral density and a high muscle mass, while others showed no correlations. The aim of this study was to identify relationships of osteophyte formation with bone mineral density and muscle mass. Methods A cross sectional study of knee osteoarthritis was conducted. Cases were classified as patients with osteophyte formation, while controls were those without osteophytes. All subjects underwent a knee x-ray and bone mineral density and body composition evaluation. General patient characteristics, covariates, and the results of biochemical analyses were also recorded. Statistical analysis was conducted using SPSS Version 22.0. Logistic regression and the chi-square test were utilized to analyze the relationships between the presence of knee osteophytes and the study variables. Results A total of 228 patients were enrolled, including 78 with osteophytes in the knee joint and 150 without. A total of 162/228 are females; knee OA is commonly explained among females. ( p = 0.001). The mean age was 73.23 ± 11.10 years in the osteophyte group and 71.86 ± 12.23 in the no osteophyte group ( p = 0.409). The mean body mass index was 24.15 ± 3.27 kg/m 2 in the osteophyte group and 23.37 ± 3.48 kg/m 2 in the no osteophyte group ( p = 0.433). More patients in the osteophyte group had hypertension ( p = 0.002), so the age group 73 years expected to have OA and hypertension along other metabolic diseases, and the femoral neck T score was higher in the osteophyte group ( p = 0.044). Logistic regression analysis showed that the male gender was associated with less osteophyte formation ( p = 0.001, odds ratio ( OR ) 0.11 (0.03–0.37)), and hypertension was associated with increased muscle loss ( p = 0.005). Femoral neck T score was associated with the presence of osteophyte formation ( p = 0.011, OR 1.98 (1.17–3.36)). Conclusions The results demonstrated an association of knee osteophyte formation with the femoral neck T score and hypertension, but no association with muscle mass. We speculated that in patients with osteophytosis and increased bone mass, metabolic factors such as hypertension should be considered. Further study of the molecular mechanisms regulating these processes is needed in the future. Key Points • Associations of knee osteophyte formation with the femoral neck T score, but not with muscle mass. • Those with osteophytosis and an increased bone mass and metabolic factors such as hypertension need to be assessed.